Social networks and their impact on marital disputes among Saudi families in Taif - Al Harthy, Talal Saad; Al Shahrani, Ayed (Journal of Humanities & Social Sciences, 2018)
The study aimed to identify the impact of social networks on marital relations and the social roles that lead to marital disputes in the Saudi family in Taif. The researcher used the descriptive approach. The tool consisted of a questionnaire of 41 words applied on a sample of 150 individuals (84) males and 66 females. Using the statistical program (SPSS), the study reached the following results: - The first aspect: the effect of the social networks on the relationship between the spouses, had the highest average (2.50 of 3) followed by the second aspect; the impact of networks on social roles between the spouses, an average of 2.48, while the third aspect; the possible means to reduce the negative effects of social networks on the relationship between the spouses with an average of 2.31. The results of the study showed that 68.7% of the sample believe that the impact of social networks on the Saudi family is very effective, while 24% believe that the networks are fairly effective and 60.7% are completely satisfied with the control developed by the government to deal with social networks, while the ratio of (34.7%) are satisfied to some extent, and a percentage of (4.7%) is not quite satisfied. Also, the results show that 31.3% of the sample use networks less than two hours per day, 30.7% use networks 2-4 hours, 22.7% use them 4-6 hours, and 15.3% use the networks (6) hours or more per day. The results showed that 42% of respondents use Twitter, 26.7% followed by Facebook, 17.3%, and 14% use Snapchat. - The results of the study showed that there were no statistically significant differences at the level of (α = 0.05) between the responses of the sample members of the study on the effect of social networks on marital conflicts according to variables (gender, marital status, age, occupation, educational level, income level). The general level of expressions in the three aspects of the study. In the light of the results of the study, a number of recommendations were presented to limit the negative impact of social networks on family life and to use them to strengthen marital relationships and to raise social awareness.